Pengaruh Variasi Konsentrasi Natrium Benzoat Terhadap Kualitas dan Daya Simpan Sirop Nanas - Tritisari, Angga; Lianto, Amir; Suhana, Suhana (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
Pineapple is a horticultural crop that is widely cultivated in Sambas Regency. Pineapples have limited storage time, so proper handling in processing can improve their quality. One method for preserving pineapple is to process it into syrup. Syrup is a drink consisting of a mixture of sugar with or without the addition of other ingredients, in accordance with applicable standards. This research aims to determine the effect of sodium benzoate concentration on pH levels, total dissolved solids, and shelf life of pineapple syrup. There were three treatments in this study, namely without adding sodium benzoate, adding 0.05 grams of sodium benzoate,  and adding 0.1 grams of sodium benzoate. The results showed that the concentration of sodium benzoate affected the pH, total dissolved solids, and shelf life of pineapple syrup. Syrup with a sodium benzoate concentration of 0.1 gram has the lowest pH, namely 6.7, and the highest total dissolved solids at 55%. The longest shelf life was also found in syrup with a concentration of 0.1 gram of sodium benzoate, namely 43 days. The best treatment based on this research is the use of sodium benzoate at a concentration of 0.1 gram.